EAP and ECPCP Statement Risks for Children's Health During the COVID-19 Pandemic and a Call for Maintenance of Essential Pediatric Services - Dembiński, Łukasz; Huss, Gottfried; Radziewicz-Winnicki, Igor; Grossman, Zachi; Mazur, Artur; del Torso, Stefano; Barak, Shimon; Carrasco Sanz, Angel; Hadjipanayis, Adamos (Frontiers in Pediatrics, 2021)
The COVID-19 pandemic and global lockdown have had drastic socioeconomic and psychological effects on countries and people, respectively. There has been limited access to health care and education. These negative consequences have had a significant impact on the well-being of children and adolescents. Therefore, the EAP and the ECPCP are requesting state, health, and education authorities as well as European pediatric societies and the healthcare professionals that special attention be given to this population and the problems they face as a result of the pandemic.